Traumatic dental injuries in 6 to 12 years old schoolchildren: a multicenter cross-sectional study in Mexico - Vicente RUEDA-IBARRA; Rogelio José SCOUGALL-VILCHIS; Edith LARA-CARRILLO; Salvador Eduardo LUCAS-RINCÓN; Nuria PATIÑO-MARÍN; Gabriel Alejandro MARTÍNEZ-CASTAÑON; Martin ROMERO-MARTÍNEZ; Carlo Eduardo MEDINA-SOLIS; Gerardo MAUPOMÉ (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of this study was to determine the prevalence of dental trauma in schoolchildren 6 to 12 years of age and associated clinical, sociodemographic, and socioeconomic variables. A cross-sectional study was conducted in 477 children from public elementary schools in four locations in Mexico. The dependent variable was dental trauma, which was dichotomized in 0 = without dental trauma and 1 = with dental trauma. For the statistical analysis, a multivariate binary logistic regression model was generated in Stata. Average age was 9.06±1.94 years and 51.1% were girls. The prevalence of dental trauma was 18.2%. Falls, automobile accidents and sports had the highest number of instances (p < 0.01). In the multivariate model, it was observed that the risk of dental trauma increased with age (OR = 1.28) and among boys (OR = 1.45). Schoolchildren with decreased overjet (OR = 0.38) had lower dental trauma. Father's age (OR = 1.03) and educational level (OR = 1.78) were associated with dental trauma. Schoolchildren without health insurance (OR = 0.62) presented dental trauma less often. This study provided important information regarding the association of different sociodemographic, socioeconomic and clinical variables with dental trauma in Mexican schoolchildren. Identifying factors associated with dental trauma may support health promotion opportunities to ameliorate the prevalence of dental trauma.